Adsorptive separation of cyclohexanol and cyclohexanone by nonporous adaptive crystals of RhombicArene. Issue 47 (26th November 2021) - Zhao, Yongye; Xiao, Hongyan; Tung, Chen-Ho; Wu, Li-Zhu; Cong, Huan
Abstract : The novel macrocycle RhombicArene features excellent capability for rapid, exclusive, and recyclable vapor adsorption of cyclohexanone in the presence of cyclohexanol, showing potential for energy-saving separation of these feedstock chemicals. Abstract : As feedstock chemicals with similar boiling points, cyclohexanol (CHOL ) and cyclohexanone (CHON ) are often obtained as mixtures during production processes. Separation of mixed CHOL and CHON is important but energy-consuming by distillation. Here we report the development of a new macrocycle RhombicArene, which forms a host–guest complex with CHON through C–H⋯π interactions and hydrogen bonds. The nonporous adaptive crystals of RhombicArene exhibit excellent capability for rapid (30 minutes), exclusive (>99.9%), and recyclable vapor adsorption of CHON in the presence of CHOL under mild and user-friendly conditions.